Fusion of a Short HA2-Derived Peptide Sequence to Cell-Penetrating Peptides Improves Cytosolic Uptake, but Enhances Cytotoxic Activity - Igor Kitanovic; Stefan Wölfl; Franziska Schramm; Kristin Löbner; Jan Hoyer; Ines Neundorf; Robert Rennert (Pharmaceuticals, 2009)
Cell-penetrating peptides (CPP) have become a widely used tool for efficient cargo delivery into cells. However, one limiting fact is their uptake by endocytosis causing the enclosure of the CPP-cargo construct within endosomes. One often used method to enhance the outflow into the cytosol is the fusion of endosome-disruptive peptide or protein sequences to CPP. But, until now, no studies exist investigating the effects of the fusion peptide to the cellular distribution, structural arrangements and cytotoxic behaviour of the CPP. In this study, we attached a short modified sequence of hemagglutinin subunit HA2 to different CPP and analysed the biologic activity of the new designed peptides. Interestingly, we observed an increased cytosolic distribution but also highly toxic activities in the micromolar range against several cell lines. Structural analysis revealed that attachment of the fusion peptide had profound implications on the whole conformation of the peptide, which might be responsible for membrane interaction and endosome disruption.